The Universal Syriac Orthodox Church of Antioch marks 1500 Jubilee Year of Mor Jacob de Serugh (St. Jacob of Serugh) - Issa, Theodora (World Council of Churches, Switzerland, 2021)
In 2021, the Universal Syriac Orthodox Church of Antioch, known of her venerated saints, the like of Ephraim the Syrian (373+), St and Martyr Fabronia (304+), is marking the 1500 Jubilee Year of Mor Jacob de Serugh (St. Jacob of Serugh).